ANALYSIS THE SMART DEMOCRACY CAR PROGRAM (MOCI) IN INCREASING THE PARTICIPATION OF FIRST-TIME VOTERS IN CIKOLE DISTRICT, SUKABUMI CITY - Dila Dwi Lestari; Dian Purwanti; Tuah Nur (RADJA PUBLIKA, 2026)
Study This analyze the influence of the Smart Car Program Democracy (MOCI) against participation voters beginners in the District Cikole , Sukabumi City . Background behind study based on the phenomenon decline participation voters in the 2024 Election by 0.19% even though the MOCI program has launched as innovation education politics . Method study use approach quantitative descriptive with stratified random sampling technique on 98 respondents voters beginner aged 17-21 years . Data collection was carried out through questionnaire and analyzed use theory James Anderson's program evaluation which includes dimensions transparency , accountability , efficiency , and effectiveness . Research results show that implementation of the MOCI program is in the category moderate (47.8%), with findings main in the form of low accessibility information (52.2% no agree ), lack of transparency program stages (49% no agree ), and inefficiency utilization source Power humans (91.8% stated lack power work ). Although Thus , this program succeed increase awareness political voters beginner , proven with 55.1% of respondents understand rights and obligations as voters . Research conclude that the MOCI program has not yet give influence significant to improvement participation voters beginner Because factor low trust to party politics and candidates as well as intensity suboptimal socialization . Recommendations​ study covers improvement transparency information , optimization human resource management , and strengthening socialization strategies digital -based for reach voters beginner in a way more effective .